Modelling an inventory management system using a system dynamic approach - Tavangar, Leila (2010)
System Dynamics (SD) is a methodology for analyzing complex systems and problems with the aid of computer simulation software. It provides a common foundation that can be applied to understand and influence how things change over the time especially in very complex systems. Inventory is one of the most visible and tangible aspects of business. Managing any manufacturing firm inventories is one of the fundamental issues to the managers. High-level inventories have both cost and benefits to the firm and having the right amount of inventory is a critical aspect. The performance of a supply chain influences the overall performance of a firm. Looking at the whole supply chain is more efficient to study the inventories. A supply chain by nature is a complex system. Parameters like new technologies, intricacy of products, and integrated supply chains enhance this complexity. Based on the problems of supply chain management and the capabilities of system dynamics in modelling complex systems, SD modelling approach was selected for this research. This thesis focuses on inventories of a Nuts and Bolts manufacturing firm supply chain in Iran. Piche Setareh Yazd (PSY) is a downstream of steel industry and all the changes in steel industry affects its supply chain. Moreover, other factors such as inflation, international sanctions and some domestic issues influence the PSY’s supply chain. All these factors in addition to the natural complexity of a supply chain make the PSY’s supply chain a good candidate for SD modelling. The model of PSY’s supply chain system developed using the system dynamics methodology. VENSIM DSS software was used for simulation of the model. The developed model was tested for usefulness, validity, and robustness with different standard tests. The tests results showed that the developed model structure is robust in different conditions and is not sensitive to the change of model parameters. Therefore, it can represent a true behavior of the PSY’s supply chain under different scenarios. This research demonstrated that SD approach is a proper tool for modelling and simulating a complex supply chain system in an instable environment. Using SD approach to model a supply chain management system could improve the understanding of managers about the true behavior of inventories and help them to make their decisions more confidently and correctly.